posted by .

solve the following differential equation:

y' + (y)tanh(x) - 2e^x = 0

  • calculus -

    First solve the homogeneous equation:

    y' + (y)tanh(x)= 0

    Replace the integration constant by an unknown function and substitute that back in the Diff. equation:

    y' + (y)tanh(x) - 2e^x = 0

    then solve for that unknown function.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus-differential equation

    Consider the differential equation: (du/dt)=-u^2(t^3-t) a) Find the general solution to the above differential equation. (Write the answer in a form such that its numerator is 1 and its integration constant is C). u=?
  2. Differential Equations

    Solve the seperable differential equation for U. du/dt = e^(5u+7t) - Using the following initial condition U(0) = 12
  3. calculus

    Solve the following differential equation: f"(x)=sinx, x(0)=0, x'(0)=1

    Using the separation of variables technique, solve the following differential equation with initial condition: (4x sqrt)(1 - t^2)(dx/dt) - 1 = 0 and x(0)=-2 I believe that the answer is one of the following two options: a.) 2x^2 = …
  5. Calculus

    Solve the differential equation dy/dx = -xe^y and determine the equation of the curve through P(1,2) I tried solving the differential equation and I get y = log(x^2/2 + C). Is this correct?
  6. Calculus

    Solve the seperable differential equation 8yyŒ =x. Use the following initial condition: y(8)=4. Express x^2 in terms of y.
  7. Calculus

    Which of the following is a separable, first-order differential equation?
  8. Help with differential eqs problem???? (Calculus)

    Consider the differential equation dy/dt=y-t a) Determine whether the following functions are solutions to the given differential equation. y(t) = t + 1 + 2e^t y(t) = t + 1 y(t) = t + 2 b) When you weigh bananas in a scale at the grocery …

    1) What are the equilibrium solutions to the differential equation and determine if it is stable or unstable with the initial condition y(-4)=1: 0.1(y+2)(4-y) 2) Use Euler's method with step size=0.5 and initial condition y(0)=3 to …
  10. Calculus

    Solve the following differential equation with initial conditions: y"=e^(-2t) + 10^(4t); y(0)=1, y'(0) = 0

More Similar Questions